Comparing WHO C-Model generated C-Section probabilities to actual delivery outcomes in a tertiary care centre - Ray, Amita; Gopi, Arun; Ray, Sujoy (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: A model which takes into account several relevant factors and gives the probability of C-Section in a woman would have the advantage of preparing for such an event. The identification of women at high risk of C-Section (>50% risk) would provide the opportunity for understanding risks involved in pursuing a vaginal delivery whereas if the risk of C-Section was less (<50%) it would prove useful in counselling for a vaginal delivery. We used the WHO C-Model with the aim to find the predictability of this model in our facility and the overuse of C-section in the 10 Robson’s Groups. Methods: A retrospective observational study in which all women who gave birth at our hospital from June 2016 to May 2017 were included and C-Section probability was calculated using the C-Model. Comparison with the actual mode of delivery was done to find the sensitivity, specificity, positive and negative predictive value of the model and the overuse of C-Section in the Robson’s Groups. Results: Out of the 314 C-Sections done only 45 women had a >50% probability, giving the model a sensitivity of 14.33%, specificity of 98.8%, positive predictive value of 90% and negative predictive value of 60.56%. Robson’s Groups 5 and 3 demonstrated the greatest overuse of C-Sections. Conclusions: The WHO Model when applied to this centre showed a high positive predictive value for C-Sections but the negative predictive value or the ability to correctly predict a vaginal delivery was much less.